(untitled) (The South East European Journal of Economics and Business, 2018)
This study examines the impact of the “institutions” on the economic development of Kosovo. Kosovo, is a newly-established independent country, and it is a transition economy since it was an autonomous region of former Yugoslavia. Based on this background, the aim of this study is to contribute to the New Institutional Economics (NIE) literature in both the nation-building and transition economies contexts. Since a detailed analysis of a single country is required, a qualitative case study was preferred as a research strategy. Different sets of secondary data were collected and analyzed by using the Qualitative Content Analysis. Findings suggested that consistent political conflicts, and lack of legitimacy of the governing bodies were the main reasons for the weak institutions and poor economic performance, due to the lack of clear reforming agenda. However, characteristics of political conflicts and lack of legitimacy differed during the state-building (1999-2007) and independence (2008 onwards) periods.